1994
DOI: 10.1002/aja.1002000106
|View full text |Cite
|
Sign up to set email alerts
|

Increased mesenchymal cell density accompanies induction of tropoelastin expression in developing elastic tissue

Abstract: We studied the differentiation of elastin-producing fetal bovine chondrocytes to understand the regulatory processes associated with induction of elastin expression. Analysis of auricular elastic cartilage development in vivo indicated that differentiation of the prechondrogenic blastema to an elastogenic phenotype was preceded and accompanied by condensation of the mesenchymal cells. In addition, induction of elastin production was temporally and spatially linked to expression of type I1 collagen and proteogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Despite this fundamental difference, only little is known about the distinct development processes that lead to these different cartilage subtypes. From embryonic development, it is known that while hyaline cartilage is present in the nose of murine embryos from day 14 on (32), elastic cartilage in the ear does not mature until late fetal and early neonatal periods (21), suggesting that developmental differences in timing and molecular signaling may attribute to cartilage subtype differentiation. More knowledge about these differential developmental processes may reveal clues for engineering specific subtypes of cartilage.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this fundamental difference, only little is known about the distinct development processes that lead to these different cartilage subtypes. From embryonic development, it is known that while hyaline cartilage is present in the nose of murine embryos from day 14 on (32), elastic cartilage in the ear does not mature until late fetal and early neonatal periods (21), suggesting that developmental differences in timing and molecular signaling may attribute to cartilage subtype differentiation. More knowledge about these differential developmental processes may reveal clues for engineering specific subtypes of cartilage.…”
Section: Resultsmentioning
confidence: 99%
“…Successful healing can best be attributed to the ability of the chondrocyte populations to assume fibrochondrocyte morphology and integrate into the surrounding tissue. 17,20 The chondrocytic type changed into a fibroblast-like cell type in the middle of the lesion. At the edges of the lesion, the chondrocytes remained in their typical round shape.…”
Section: Discussionmentioning
confidence: 99%
“…40,47 However, the analysis of the reconstructed elastic cartilages indicated that production of the matrix macromolecules, including elastin, decline with the age of the donor, supporting the concept of ''age programs'' for the biosynthesis and turnover of different matrix macromolecules. 8,37,48,49 It has also been established that auricular chondrocytes isolated from human cadaver elastic cartilage increase their in vitro proliferation and matrix production containing elastin when maintained in very dense cultures 29 or in response to basic fibroblast growth factor and transforming growth factor ␤.…”
Section: Discussionmentioning
confidence: 98%
“…Studies with human hyaline chondrocytes also established that the number of cells initially harvested can be greatly increased by an additional cell cultivation in vitro, 2,10 especially when stimulated with insulin, dexamethasone, or growth factors such as bFGF, PDGFbb, EGF, and IGF. 11,12 It has also been established that facilitating cell-cell interactions in a very dense cell seeding in the initial cultures 7,29 or cell aggregation in rotating culture vessels 16,28 may prevent chondrocyte dedifferentiation toward fibroblast-like cells in long-lasting monolayer cultures. 9,37 Most importantly, it has been shown that cartilages can be created in predetermined shapes and dimensions using chondrocyte transplantation on appropriate polymer templates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation